Gender and human resources for health in South Asia : challenges and constraints - International Workshop on Gender and Human Resources for Health: Capacity Development Through Education and Training (2004 : Dhaka, Bangladesh); Ullah, M. Mahbub; Islam, Anwar; Bangladesh. University Grants Commission; Canadian International Development Agency (Dhaka : Jointly published by the University Grants Commission of Bangladesh & Canadian International Development Agency, Canada, 2006)
International Workshop on Gender and Human Resources for Health: Capacity Development Through Education and Training held at Dhaka on 13-14 Oct. 2004.
Includes bibliographical references.
Includes bibliographical references.
Keywords: Public health -- South Asia; Medical care -- South Asia